MENINGKATKAN PROFESIONALISME GURU DAN MUTU PEMBELAJARAN MELALUI IMPLEMENTASI MANAJEMEN SUPERVISI KLINIS - Yohanes Umbu Lede (SekolahTinggi Keguruan dan Ilmu Pendidikan (STKIP), 2017)
The research aimed to know the clinical supervission management to improve teacher’s professionalism and learning quality. Results of the research showed that: (1) Clinical supervision management to improve teachers professionalism and learning quality was successful. Supervission management in grew continuously and systematically. Supervisors understand and know about clinical supervision properly, help and guidance teachers with aims for learning emendation. (2) Professional competence of teachers which felt needs to understood and well known are competences of professional teachers based on vision and mission in school. The competences mentioned is suitable with school vision and mission based on leadership competence. (3) Supporting factors in the management of clinical supervision include a culture and school management, initiative and transparency of a teacher, and human resources that support, institution staffs and foundation give PKG and FDG socialization, and evaluation activities. (4) Constraints factors in implementation of clinical supervision management are: erroneous paradigms about clinical supervision (supervision is still looked and understood as an assessment for a teacher performance), time for teaching is demanding schedule, there are unnatural situation and action in the class, there are some teachers don’t have openhanded when under strict, there are psychology constraint, and achievable of usingtechnology based on IT.